Épocas de poda na sazonalidade, produção e qualidade dos frutos da goiabeira 'Paluma' - Ramos, Dayana Portes [UNESP]; Leonel, Sarita [UNESP]; da Silva, Andrea Carvalho; de Souza, Manoel Euzebio [UNESP]; de Souza, Adilson Pacheco; Fragoso, Alexandre Martins (Universidade Estadual de Londrina (UEL), 2011)
The purpose of the research was to evaluate the yield and quality of the 'Paluma' guava fruits submitted to the pruning in the June and July months/2007, in Botucatu, São Paulo state, Brazil. Number of fruits, fresh weight, longitudinal and transversal diameter, yield per plant, productivity, soluble solid (SS), acidity (AT), ratio (SS/AT), pH, content ascorbic acid, and total reducing sugars of the fruits were evaluated. The experimental design was completely randomized consisting of 3 treatments (2 times of pruning + control), with 12 replications for each treatment. It was observed that the guava trees which were not pruned showed, higher yield per plant (145.75 kg), yield (60.72 t ha(-1)) and, number of fruits per plant (1.163), when pruned in June and July. Regarding the quality of the fruit most of the variables were not affected by treatments, except for reducing sugars. The cycle between the pruning until early harvest concentrated fruit ranged from 197 to 234 days, and pruning in June had the smallest period.
Pruning times in seasonality, yield and quality of 'Paluma' guava fruits
Keywords: Psidium guajava; climate; soluble solids; acidity